2011
DOI: 10.1007/s12603-011-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant micronutrients improve intrinsic and UV-induced apoptosis of human lymphocytes particularly in elderly people

Abstract: Young and elderly people have a higher intrinsic apoptosis than children, which was improved by antioxidant supplementation. UV-induced damage was attenuated by the supplementation in all three age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In that study, Ma et al reported that supplementation with moderate amounts of retinol, b-carotene, a-tocopherol, ascorbic acid, and selenium for 8 weeks was protective; however, the level of protection in the present study was much more dramatic. 22 The present study definitively demonstrates that the novel nutrient and phytonutrient blend dramatically impacted the DNA damage response ADM, protecting against UVR-induced cell death as evidenced by a > 50% reduction in apoptosis after 8-week supplementation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In that study, Ma et al reported that supplementation with moderate amounts of retinol, b-carotene, a-tocopherol, ascorbic acid, and selenium for 8 weeks was protective; however, the level of protection in the present study was much more dramatic. 22 The present study definitively demonstrates that the novel nutrient and phytonutrient blend dramatically impacted the DNA damage response ADM, protecting against UVR-induced cell death as evidenced by a > 50% reduction in apoptosis after 8-week supplementation.…”
Section: Discussionsupporting
confidence: 58%
“…Average age of participants was 58 (range of 43-75 years). Average BMI was 27 kg/m 2 (range of [19][20][21][22][23][24][25][26][27][28][29][30]. No participants withdrew from the study, and average supplement compliance was 97.3% (range of 87-100%).…”
Section: Resultsmentioning
confidence: 99%
“…46 Lymphocytes from healthy elderly people have been shown to be more prone to intrinsic apoptosis than those from children. 59 When older adults were supplemented with a cocktail of vitamins and micronutrients (3000 IU retinol, 1.5 mg β-carotene, 200 mg α-tocopherol, 500 mg ascorbic acid, and 400 μg selenium), a significant reduction in both intrinsic and UV-induced apoptosis in lymphocytes was observed. This is in agreement with another study, which showed that a mixture of vitamins and minerals could reduce intrinsic and hydroperoxide-induced DNA damage in lymphocytes from old adults.…”
Section: Combination Of Multiple Vitamins and Trace Elementsmentioning
confidence: 99%
“…Elderly individuals, therefore, become more vulnerable to pathological conditions related to oxidative stress and may require an extra supply of dietary antioxidants to combat free radicals [41]. Previous studies by our research group and by other workers have shown that neuroendocrine and immune disorders due to the aging process may be ameliorated by supplementation with melatonin, serotonin, and/or their precursor, the amino acid tryptophan [4246].…”
Section: Chronobiology: At the Cutting Edge Of Health Sciencesmentioning
confidence: 99%